From old regime to industrial state a history of German industrialization from the eighteenth century to World War I - Tilly, Richard H. (Markets and governments in economic history., 2020)
"In From Old Regime to Industrial State, Richard H. Tilly and Michael Kopsidis question established thinking about Germany's industrialization. They begin their assessment earlier than previous studies have, reaching back to the 18th century to explore the circumstances that ultimately allowed the nation to catch up with its neighbors. While some hold that Germany experienced a sudden breakthrough to industrialization, the authors instead consider a long view, incorporating market demand, agricultural advances, and regional variations in customs and governance. Tilly and Kopsidis show how the 18th-century emergence of international trade and the accumulation of capital by merchants fed commercial expansion and innovation. To fully assess the transformation, the authors offer three key factors: first, the expansion of rural industry and the commercialization of economic relationships; second, the gathering of skilled craftsmen into centralized workshops, the mercantile skills of early entrepreneurs, and agricultural improvements in response to market demand; and third, the emergence of civil service bureaucracies who could monitor and communicate material conditions across individual states. This book provides the history behind the modern German economic juggernaut"--